'GREETINGS, CICERO!': CAESAR AND PLATO ON WRITING AND MEMORY. (27th December 2018) - Krebs, Christopher B.
Abstract : In his digression on the Gauls in Book 6 of the Gallic War, Caesar includes a portrait of the Druids ( BGall. 6.13.3 sed de his duobus generibus [ sc. quae aliquo sunt numero atque honore ] alterum estdruidum ) and their public roles first and foremost in religious and legal affairs (6.13.4–5 illirebus diuinis intersunt, sacrificia publica ac priuata procurant, religiones interpretantur … fere de omnibuscontrouersiis publicis priuatisque constituunt ), not forgetting their philosophical doctrine (6.14.6 multa …disputant et iuuentuti tradunt ). He emphasizes the strictly oral form their teaching takes (6.14.4), how 'they do not deem it appropriate to commit it [their learning] to writing even though in almost everything else, in public and private affairs, they resort to Greek writing ( neque fas esse existimantea litteris mandare, cum in reliquis fere rebus, publicis priuatisque rationibus Graecis litteris utantur )', about the reasons for which he then proceeds to speculate (6.14.4):idmihi duabus de causis instituisseuidentur, quod neque in uulgum disciplinam efferri uelint neque eos qui discunt litteris confisos minus memoriae studere: quodfere plerisque accidit, ut praesidio litterarum diligentiam in perdiscendo ac memoriam remittant. This [ sc . practice] they seem to me to have instituted for two reasons: they do not wish either that their teaching be revealed to the general public or that those who are learning it, having become reliant on writing, give less attention to memorization; and it does, as a rule, happen to many that, because of the prop offered by writing, they relax their diligence in thoroughly committing things to memory.